New Zealand's Exchange Rate Cycles: Impacts and Policy - Gemma Mabin (New Zealand Government, The Treasury, 2011)
This paper explores the impact of New Zealand's exchange rate variability on the tradable sector, and policy options for dampening exchange rate variability. It finds that exchange rate variability in the medium term is likely to have a negative impact on the tradable sector. However, the link between exchange rate variability and the performance of the tradable sector is not automatic; many factors are at work. New Zealand's tradable and non-tradable sector trends are mirrored in some other countries with varying degrees of exchange rate variability. This suggests that exchange rate variability may explain part of the story as to why New Zealand's tradable sector has underperformed, but it cannot tell the whole story. This paper recognises the significant negative impact that a sustained high level of the exchange rate can have on the tradable sector. There are no easy or obvious ways to reduce exchange rate variability without some costs. This paper first explores alternative exchange rate regimes, and finds that the freely- floating exchange rate regime is still the most appropriate for New Zealand. Second, this paper explores ways to reduce exchange rate variability within the existing framework. While there are no silver bullets available to reduce exchange rate variability within the existing framework, fiscal policy and housing policy are worth pursuing in this respect, with the possibility for macro-prudential policy to play a small role in stabilising the cycle.
Keywords: F31; 330; Exchange rate; medium-term variability; tradable sector; exchange rate policy; currency union; foreign exchange intervention; Wechselkurspolitik; Wechselkurs; Volatilität; Konjunkturstatistik; Neuseeland